Research on Negotiation Strategies and Challenges in International Business Transactions - Zhang, Zhongqi (Transactions on Economics, Business and Management Research, 2024)
The complexity of international commercial transactions has increased due to market globalization, necessitating the development of effective negotiation strategies for success. This study investigates various negotiation methods and challenges faced in international commercial transactions. By synthesizing data from case studies, surveys, and existing literature, the study identifies major factors influencing negotiation outcomes, including cultural differences, legal frameworks, economic contexts, and power dynamics. The research emphasizes the importance of cross-cultural competency and adaptive negotiation techniques to navigate diverse business environments successfully. It also addresses common obstacles such as communication barriers, differences in business etiquette, and trust-building issues. The findings suggest that successful negotiators employ a combination of thorough preparation, cultural sensitivity, and strategic flexibility to achieve favorable outcomes. This study contributes to the field by providing a comprehensive analysis of the multidimensional nature of international negotiations and offering practical insights for practitioners aiming to enhance their negotiation effectiveness in a globalized economy. Future research should focus on integrating primary data to refine these strategies further and adapt them to evolving global market conditions.